Design and implementation of the 'separation of powers governance model' at the local sphere of government : the case of the City of Johannesburg Metropolitan Municipality - Chikwema, S.; Wotela, K. (International Conference on Public Administration and Development Alternative (IPADA), 2019)
In 2005, the City of Johannesburg metropolitan municipality adopted the 'separation of powers' governance model that separates the executive and legislative functions of the Council to improve governance at local level. Despite this, we are not certain if separating legislative and executive functions of a municipality improves governance at local level. Therefore, it became prudent to assess this intervention. To do this, Chikwema and Wotela (2016) developed an interpretive and conceptual framework whose summary we share in this paper. Based on this proposed research framework, this paper shares some empirical evidence on the design and implementation arrangements of the 'separation of powers governance model' in the City of Johannesburg. Specifically, we interrogate the design of the 'separation of powers' governance model in the municipality, it's structures, powers and functions as well as its implementation arrangements. Other aspects that we look into are available resources and capacity for oversight leading us to outline its activities and procedures. This interrogation provided for establishing the logic underlying the 'separation of powers' governance model in the City of Johannesburg. We conclude that the overall review of governance arrangements and subsequent implementation of the 'separation of powers' governance model in the City of Johannesburg can be understood within the context of the democratic theory of governance. However, institutionalism is a more appropriate framework to explain the findings on the overall structure and configuration of the legislature in the City of Johannesburg. We also use the principal-agent theory to interrogate the implementation arrangements (processes and procedures) implemented to effect oversight, accountability, and public participation.
The 4th Annual International Conference on Public Administration and Development Alternatives 03 - 05 July 2019, Southern Sun Hotel, OR Tambo International Airport, Johannesburg, South Africa
Keywords: Accountability; Design; Governance; Oversight; Transparency; Participation; Delegation of powers; Delegated legislation; Corporate governance